POSSIBILITIES FOR ANTIEPILEPTIC DRUGS USE IN THE TREATMENT OF TIC HYPERKINESIS AND TOURETTE SYNDROME IN CHILDREN - V. P. Zykov; E. A. Kashirina; Yu. V. Naugol’nykh (Русский журнал детской неврологии, 2017)
Objective: to evaluate the efficacy of topiramate at a dose of 1–2 mg/kg in 34 patients aged 7–17 with tic hyperkinesis and Tourette syndrome (TS).Materials and methods. We performed clinical evaluation of hyperkinesis severity along with the assessment of somatosensory evoked potentials (SSEP) and the analysis of surface electromyography (EMG) data prior to treatment initiation and after 6 weeks of therapy. SSEP investigation was carried out in accordance with a standard protocol. Interpeak latencies on the tracks Cp–Fpz (D, S), Cerv6–Fpz (D, S), Erb’i–Erb’c (D, S) were evaluated in order to determine the afferentation between relevant brain structures: N9–N13, N13–N20, N9–N20. N20–P23 potentials reflected primary activity of somatosensory cortex. The investigation of tic hyperkinesis was conducted using surface EMG of facial muscles (m. orbicularis oculi), the muscles of the shoulder girdle (m. supraspinatus), and the muscles of the upper extremities (m. flexor digitorum superficialis) according to the standard protocol. Interference curve was recorded at rest and after hyperkinesis stimulation with the use of provocative tests. High-amplitude (more than 500 mkV) oscillations were considered as burst activity. The severity of clinical manifestations was evaluated using the Yale Global Tic Severity Scale (1989) and the method of tics counting during 20 minutes (V.P. Zykov, 2009). The control group comprised 15 healthy children matched for sex and age.Results. The use of topiramate in patients with chronic motor/vocal tics and TS has significantly decreased the severity of hyperkinesis manifestations, evaluated both by the Yale Global Tic Severity Scale (p < 0,05) and by the method of tics counting during 20 minutes (p < 0,05). It also helped to decrease the prevalence of burst activity in EMG while registering hyperkinesis in different muscle groups. SSEP data showed the normalization of interpeak latency values and the decrease of N20–P23 potentials amplitude, which reflects the decline in the activity of brain somatosensory system, represented by thalamo-cortical structures.Conclusion. Surface EMG and SSEP methods can be used for evaluation of treatment efficacy in cases of tic hyperkinesis and TS.